LncRNA modulates Hippo-YAP signaling to reprogram iron metabolism - Xin-yu He; Xiao Fan; Lei Qu; Xiang Wang; Li Jiang; Ling-jie Sang; Cheng-yu Shi; Siyi Lin; Jie-cheng Yang; Zuo-zhen Yang; Kai Lei; Jun-hong Li; et al. (Nature Communications, 2023)
Abstract Iron metabolism dysregulation is tightly associated with cancer development. But the underlying mechanisms remain poorly understood. Increasing evidence has shown that long noncoding RNAs (lncRNAs) participate in various metabolic processes via integrating signaling pathway. In this study, we revealed one iron-triggered lncRNA, one target of YAP, LncRIM (LncRNA Related to Iron Metabolism, also named ZBED5-AS1 and Loc729013), which effectively links the Hippo pathway to iron metabolism and is largely independent on IRP2. Mechanically, LncRIM directly binds NF2 to inhibit NF2-LATS1 interaction, which causes YAP activation and increases intracellular iron level via DMT1 and TFR1. Additionally, LncRIM-NF2 axis mediates cellular iron metabolism dependent on the Hippo pathway. Clinically, high expression of LncRIM correlates with poor patient survival, suggesting its potential use as a biomarker and therapeutic target. Taken together, our study demonstrated a novel mechanism in which LncRIM-NF2 axis facilitates iron-mediated feedback loop to hyperactivate YAP and promote breast cancer development.